A study on English Teachers' Conceptions of Grammar Teaching and Classroom Practices in West Shoa Zone High schools, Ethiopia - Haile haile mekonin; Adinew Tadesse Degago; Abera Admassu; 4Alemayehu Getachew (LPPM Universitas Advent Indonesia, 2026)
This study examines English teachers' conceptions of grammar teaching methods in secondary schools across West Shoa Zone, Oromia Regional State, Ethiopia. Teachers’ beliefs about grammar instruction significantly influence their lesson planning and instructional strategies. A total of 120 English language teachers from 18 government secondary schools were selected using a census technique. A concurrent mixed-methods research design was employed, utilizing questionnaires and interviews for data collection. The qualitative data were analyzed through verbatim transcription, while the quantitative data were examined using descriptive statistics, including frequency, mean, and percentage. Findings revealed that teachers predominantly adhered to traditional grammar teaching approaches, positioning themselves as the primary source of knowledge while treating students as passive recipients. This reliance on conventional methods suggests a limited integration of communicative and student-centered strategies in grammar instruction. The study highlights the need for pedagogical shifts toward more interactive and learner-centered approaches to enhance grammar teaching effectiveness..